UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN TEMATIK PADA PELAJARAN IPA, BAHASA INDONESIA, MATEMATIKA DAN SBK KELAS II SEKOLAH DASAR - Darmawan Nugroho, Imam; Priatna, Asep (STKIP Subang, 2016)
Conducted thematic learning in primary schools, especially low grade since the passing of the SBC in 2006, there are still many obstacles in the field and not in accordance with the provisions of Permendiknas Content Standards No.22 of 2006 and it therefore requires an effort of applying thematic learning in accordance with Standards The content and improve the quality of learning. In this research theme selected based on the needs of learning and research interests are focused primarily on assessing learning science, Indonesian, mathematics, and SBK through thematic learning. The purpose of this study was to determine the general process of learning science, Indonesian, mathematics, and SBK through thematic learning model, particularly with regard to the learning outcomes and student activity. This study uses a class action consisting of 2 cycles of action. The research found that students' understanding before action learning cycle I showed low criteria with the average achieved 47.96 and the second cycle showed normal criteria with average achieved 55.11. After the act of learning, comprehension of students has increased that the first cycle the average value of students with the acquisition of 66.11 indicates that students 'understanding of normal, while in the second cycle students' understanding increased with the acquisition of 71.48. Thus, the application of thematic learning model can be more effectively used to improve learning outcomes and student activity grade II compared to non-thematic learning.